2004
DOI: 10.1093/ageing/afh017
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and risk assessment tools for falls in hospital in-patients: a systematic review

Abstract: A small number of significant falls risk factors emerged consistently, despite the heterogeneity of settings namely gait instability, agitated confusion, urinary incontinence/frequency, falls history and prescription of 'culprit' drugs (especially sedative/hypnotics). Simple risk assessment tools constructed of similar variables have been shown to predict falls with sensitivity and specificity in excess of 70%, although validation in a variety of settings and in routine clinical use is lacking. Effective falls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
497
1
51

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 605 publications
(561 citation statements)
references
References 62 publications
12
497
1
51
Order By: Relevance
“…31 The most consistently reproducible patient-related risks are altered mental status (including cognitive impairment and depression), altered mobility (particularly lower limb weakness), a history of falls, and toileting needs. 13,[32][33][34][35][36] Less consistency is seen with other traditional risk factors such as age, sedating medication, and length of stay. 5,13,32,[36][37][38] Attempting to risk-stratify patients using simple and accurate assessment tools developed from these risk factors has proven to be very difficult.…”
Section: Dibardino Et Al |mentioning
confidence: 99%
See 2 more Smart Citations
“…31 The most consistently reproducible patient-related risks are altered mental status (including cognitive impairment and depression), altered mobility (particularly lower limb weakness), a history of falls, and toileting needs. 13,[32][33][34][35][36] Less consistency is seen with other traditional risk factors such as age, sedating medication, and length of stay. 5,13,32,[36][37][38] Attempting to risk-stratify patients using simple and accurate assessment tools developed from these risk factors has proven to be very difficult.…”
Section: Dibardino Et Al |mentioning
confidence: 99%
“…Many tools have been developed based on identified risk factors, but perform very poorly when trying to identify patients who will fall with reasonable specificity and positive predictive value. 34,[39][40][41][42][43][44] In fact, it has been demonstrated that using a nurse's judgment, a physician's opinion based on a patient's likelihood to wander or a simple 2-question tool have all performed better than sophisticated risk calculators. 33,45,46 Therefore, it is possible that interventions could benefit from including all patients, with de-emphasis on unproven risk stratification tools.…”
Section: Dibardino Et Al |mentioning
confidence: 99%
See 1 more Smart Citation
“…How attention is divided between two simultaneously performed tasks mainly depends on the efficiency of executive function (14,15 (14) also showed an association between low stride time variability and efficient executive function, and Sheridan et al (15) reported a relationship between high stride time variability and impaired executive function -both powerful predictors of falling (14)(15)(16)(17)(18). Among the small number of fall risk factors consistently found in geriatric inpatients, gait instability was identified as one of the most important (6). However, in all inpatient studies, the diagnosis of unstable gait was always based on clinical impressions and arbitrary appreciation without any biomechanical quantification of the gait disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review of hospital fall prevention programs, Oliver et al (6) found an intervention-related reduction in fall rates of 25%. Identifying patients at high risk of falling is the first step in designing targeted fall prevention programs (4,6).…”
Section: Introductionmentioning
confidence: 99%